Differential Cytotoxicity of Rooibos and Green Tea Extracts against Primary Rat Hepatocytes and Human Liver and Colon Cancer Cells – Causal Role of Major Flavonoids. (26th November 2021) - Samodien, Sedicka; Kock, Maryna de; Joubert, Elizabeth; Swanevelder, Sonja; Gelderblom, Wentzel C. A.
Abstract: Differential anti-proliferative and pro-apoptotic effects of aqueous extracts of green rooibos (Rg; Aspalathus linearis ) and green tea (GT; Camellia sinensis ) and an aspalathin-enriched extract of green rooibos (GRE), were investigated in primary rat hepatocytes (PH) and human liver (HepG2) and colon (HT-29) cancer cells. Rooibos flavonoids, aspalathin and luteolin, and the green tea flavanol, epigallocatechin gallate (EGCG), were included to assess their contribution relative to their extract concentrations. GRE was the most effective in reducing cell growth parameters which was associated with a high total polyphenol content and high ferric reducing potential. Differential cell responses were noticed with HepG2 cells more sensitive than PH toward the induction of apoptosis by GRE. Luteolin induced apoptosis in PH and HepG2 cells while aspalathin lacked any effect. EGCG induced apoptosis in HepG2 cells while PH were resistant. HT-29 cells were resistant to apoptosis induction by the tea and pure flavonoids. Differences existed in the individual effects of the major rooibos and GT flavonoids against cell growth parameters compared to their equivalent concentrations in the extract mixtures. Diversity of the flavonoid constituents, physicochemical properties and cellular redox status governing cell survival are likely to explain the differential cell responses.